ANALISIS KESALAHAN PENGGUNAAN PARTIKEL NI DAN DE MAHASISWA ANGKATAN 2020 PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNRI DALAM PEMBELAJARAN SAKUBUN - Dewi Kartika; Merri Silvia Basri; Adisthi Martha Yohani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research aims to determine the factors that cause errors in the use of ni and de particles in sakubun learning. This research is a qualitative descriptive study. Data were analyzed by using method by Setyawati (2010). Richard (dalam Tarigan, 2011), and Jain&Fisik (dalam Tarigan, 2011). A total of 6 students of Japanese Language Education FKIP UNRI who became the data in this study. The data was taken from interviews to find out what causes errors that occur in sakubun learning. Research results show that. The errors that arise are caused by a lack of the student understanding of the material, especially the ni and de particles. In addition, this errors occurs due to a performance factor, namely the lack of concentration of student when writing essays. Lack of concentration can cause students to not be able to do well.Key Words: Error Analysis, Particle, Sakubun